USING BOOKMARK TECHNIQUE TO IMPROVE THE RECOUNT TEXT READING SKILL OF THE TENTH GRADERS OF MAN PARAKAN TEMANGGUNG IN THE SCHOOL YEAR 2015/2016 - Ambarwati Ambarwati; Sukarno Sukarno; Sisworahardjo Sisworahardjo (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2018)
Reading is a must in language learning. In Senior High School, it is not an exception. The main problem is that the students are not interested in doing the reading task. They also have low motivation. It is caused by the monotonous way of teaching. There are two objectives of this research. They are to know whether the use of bookmark technique can increase the learning motivation in the recount text reading and to know how great the improvement of the recount text reading skill of the students who are taught using bookmark technique is. The writer conducted a Classroom Action Research (CAR). It was divided into three phases, pre-cycle, cycle I and cycle II. The writer took the tenth graders of MAN Parakan Temanggung as the subject of the research. The techniques used to collect the data were tests and non-test technique. The writer used the average score and percentage in each cycle to analyze the data. The result of the tests shows that the mean score of the students increase.